NILAI PENDIDIKAN KARAKTER DALAM CERITA KOTA EMAS KARYA ISHAK SAMUEL KIJNE - Rumainum, Merry Ch. (JURNAL TRITON PENDIDIKAN, 2016)
This research uses qualitative descriptive with the the literay short story of âGolden Cityâ by Ishak Samuel Kijne as the object of the research. This research aims to uncover the values of education character in the story based on eighteen values of educative character promoted by the ministry of National education 2010.In this research the writer used two theories, and one approach. Theories used were behaviorism theory and hermeneutic Recour theory in order to discuss the interpretation of the text, while the approach used was the contextual approach where students will be interested to learn as far as the media used are close to them. These theories and the approach were used to solve the problems of the research.The results of research show that there are sixteen values of educative charater found in the object of the research including religious value, honesty, tolerance or respect, hardwork, creativity, autonomy, curiosity, accuracy, respective achievement, coorperation, peaceloving, environtmental care, social care and responsiblity.